2013
DOI: 10.1136/jnnp-2013-306237
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state fMRI study on drug-naive patients with Parkinson's disease and with depression

Abstract: Our study demonstrates that PD-Dep patients are characterised by increased regional spontaneous neural activity in the orbitofrontal area and decreased functional integration within the prefrontal-limbic network. These findings may be helpful for facilitating further understanding of the potential mechanisms underlying depression in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 39 publications
4
68
2
1
Order By: Relevance
“…More recent striatal connectivity studies have supported some of these findings, such as decreased corticostriatal functional connectivity with the putamen in PD (Luo et al, 2014). However, there have also been important differences.…”
Section: Neuroimaging Of Pdmentioning
confidence: 81%
See 1 more Smart Citation
“…More recent striatal connectivity studies have supported some of these findings, such as decreased corticostriatal functional connectivity with the putamen in PD (Luo et al, 2014). However, there have also been important differences.…”
Section: Neuroimaging Of Pdmentioning
confidence: 81%
“…Vriend et al (2014a) reviewed neuroimaging studies of depression in PD and highlighted decreased dopaminergic function in the ventral striatum. MRI studies of co-morbid depression in PD have also shown alterations in ALFF and morphometric result although they are notable for some inconsistent results in ALFF results (Luo et al, 2014a; Skidmore et al, 2013b; Wen et al, 2013) and morphometric studies (Surdhar et al, 2012; van Mierlo et al, 2015). …”
Section: Neuroimaging Of Pdmentioning
confidence: 99%
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, structural neuroimaging techniques have shown gray matter loss and white matter abnormalities in the prefrontal, temporal, and some limbic regions in depressed PD patients [ 28 , 29 ]. Finally a very recent resting-state functional magnetic resonance study (RS fMRI) revealed reduced functional connectivity in the prefrontal-limbic network in PD patients with depression as compared with PD patients without [ 30 ].…”
Section: Pathophysiologymentioning
confidence: 97%